1999
DOI: 10.1177/104649649903000504
|View full text |Cite
|
Sign up to set email alerts
|

A Tripartite Model of Group Identification

Abstract: Group identification is defined as member identification with an interacting group and is distinguished conceptually from social identity, cohesion, and common fate. Group identification is proposed to have three sources: cognitive (social categorization), affective (interpersonal attraction), and behavioral (interdependence). Inconsistent use of the term and problematic measurement mar existing literature on group identity and group identification. A new group identification scale, composed of three subscales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 50 publications
4
157
1
4
Order By: Relevance
“…Генри и др. выделили когнитивный, аффективный и поведенческий аспекты в групповой идентификации [12]. Обобщение иссле-дования межличностной и групповой идентификации позволяет сделать неко-торые выводы.…”
Section: эмпирические исследованияunclassified
“…Генри и др. выделили когнитивный, аффективный и поведенческий аспекты в групповой идентификации [12]. Обобщение иссле-дования межличностной и групповой идентификации позволяет сделать неко-торые выводы.…”
Section: эмпирические исследованияunclassified
“…Smerilli (2012) developed this idea further by proposing an extension of the theory in which players use the Bdouble-crossing intuition^as a basis for adjudicating between individual and team reasoning. Furthermore, experimental evidence has shown that perceived interdependence, as produced by a threat of negative outcomes from dissimilarcategory others or a promise of positive outcomes from similar-category others, is a stronger driver of group identification than mere similarity or enhanced salience of group identity (Flippen, Hornstein, Siegal, & Weitzman, 1996;Henry, Arrow, & Carini, 1999). This is a rather different interpretation of interdependence from Bacharach's strong interdependence, but the conclusion may apply also to strong interdependence, and the comparison would be well worth investigating experimentally.…”
Section: Group Identificationmentioning
confidence: 99%
“…Team identification is defined as a personal, cognitive, emotional and behavioral bond between individual and team (Henry, Arrow, & Carini, 1999). Team identification is a particular type of social identification, representing the extent to which individual team members perceive a sense of ''oneness'' with a particular organizationally based team (Gundlach et al, 2006).…”
Section: Moderating Effect Of Team Identitymentioning
confidence: 99%
“…Team identification was measured by the 12-item 7-point Likert-type inventory (7 ¼ strongly agree, to 1 ¼ strongly disagree) developed by Henry et al (1999) (e.g., ''I think of this team as part of who I am''). Internal consistency reliability was 0.92. members adopt active collaboration among parties to reach a solution that satisfies all concerned (e.g., ''Team members try to bring all our concerns out in the open so that the issues can be resolved in best possible way'').…”
Section: Team Identitymentioning
confidence: 99%